The role of Mahua literature in shaping Malaysian cultural identity and historical discourse - Chin, Tan Kok; Ser, Wu Hiong; Chin, Mooi San (Transnational Press London, 2024)
This research paper examines the significant influence of Mahua (Chinese-Malaysian) literature on the formation of Malaysian cultural identity and historical discourse. The study investigates the emergence of Mahua literature as a counter-narrative to the prevailing Malay-centric literary tradition, portraying the challenges and aspirations of the Chinese-Malaysian community. This research examines the intricate relationship between Mahua and Malay literature in Malaysia, revealing the power dynamics that have influenced the country's national identity. It employs Kekes's theory of pluralism, Foucault's discourse analysis, and Tansley's ecosystem concept to analyse this interplay. The paper also examines the influence of Malay nationalism on the growth of national literature, emphasising the language-focused prejudices that have marginalised Mahua literature. This study promotes a broader and more diverse approach to national literature by conducting a thorough comparative analysis of prominent literary figures and their works. It emphasises the importance of recognising the contributions made by all ethnic communities. The research findings have profound implications for understanding the role of minority literature in postcolonial countries and fostering cultural diversity within national literary traditions.